Analisa Kemanfaatan Dan Kemudahan Terhadap Penerimaan Sistem OPAC Menggunakan Metode TAM - Kharismaya, Citra; Dewi, Linda Sari; Arisawati, Ester; Handayanna, Frisma (STIKOM Tunas Bangsa Pematangsiantar, 2017)
This study describes the reception OPAC Davis 1989 TAM variables namely perceived usefulness (perceived benefit), perceived ease of use (ease perceived) and accepted (acceptance) OPAC. In this study, data were collected through a questionnaire using Likert scale to 100 users si¬stem den response OPAC (Online Public Access Catalog). Sampling technique used is purposive sampling to determine the level of acceptance of the system OPAC (Online Public Access Catalog). Quantitative analysis includes the validity, reliability. In the classic assumption test, used test for normality, multicollinearity and heterokedastisitas with F and t hypothesis testing. Multiple linear regression analysis is used to determine the effect of the independent variables with the dependent variable. The results showed that perceived usefulness and perceived ease have a significant effect on the acceptance by the user system (R Square) amounted to 40.8%.